(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The paper explores Edgar Dale’s contribution to developing and effectively using teaching and learning materials. Edgar Dale’s model, designed to represent different levels of abstraction in learning, remains an essential framework for teaching design and teaching practices. This paper emphasizes the conceptual foundation of the Cone of Experience and its influence on teaching strategies. The study examined the impact of the model on material design and student involvement and assessed its relevance in contemporary teaching. This article also discusses how the experience funnel facilitates a broader understanding of experiential learning in various educational environments.